El Extremo Oriente y la condición del indio en el siglo XVI - Marco Antonio Urdapilleta Muñoz (Ciencia Ergo Sum)
This article seeks to verify that during the process of historical concretion of the New World and its inhabitants during the XVI century, differentiation from the nations and inhabitants of East Asia played an important role. Although the idea of the Asian condition of America, the Fourth Part of the World, was soon abandoned, the newly discovered world continued to be interpreted from the perspective of some elements that characterized the East Indies. In this sense, that region continued to be a cultural, geographical and historical reference pattern for the Americas